La extracción de conocimiento y terminología a partir de corpus ad hoc: el uso de documentos digitales de la web pública - Sánchez-Gijón, Pilar (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Electronic communication accelerates the exchange of knowledge and information in areas of specialized knowledge. This state of affairs forces anyone involved in such communication (e.g. technical writers, technical translators) to remain up to date with new developments. Not only do professionals belonging to this group of people have to master the standard terminology of each specialized domain, they must also assimilate and understand the subject matter within which they are working. This article proposes a method for assembling and using specific corpora with a view to extracting from them systematic and bilingual knowledge relating to terminology, the conceptual relations between terms, and the knowledge that they represent. Special attention is devoted to the strategies that will enable professionals to use such corpora in English and in Spanish.